Defining Incidence of Acute Compartment Syndrome in the Research Setting: A Proposed Method From the PACS Study. (January 2022) - Leroux, Andrew; Frey, Katherine P.; Crainiceanu, Ciprian M.; Obremskey, William T.; Stinner, Daniel J.; Bosse, Michael J.; Karunakar, Madhav A.; O'Toole, Robert V.; Carroll, Eben A.; Hak, David J.; Hayda, Roman; Alkhoury, Dana; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To compare the retrospective decision of an expert panel who assessed likelihood of acute compartment syndrome (ACS) in a patient with a high-risk tibia fracture with decision to perform fasciotomy. Design: Prospective observational study. Setting: Seven Level 1 trauma centers. Patients/Participants: One hundred eighty-two adults with severe tibia fractures. Main Outcome Measurements: Diagnostic performance (sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver–operator curve) of an expert panel's assessment of likelihood ACS compared with fasciotomy as the reference diagnostic standard. Secondary Outcomes: The interrater reliability of the expert panel as measured by the Krippendorff alpha. Expert panel consensus was determined using the percent of panelists in the majority group of low (expert panel likelihood of ≤0.3), uncertain (0.3–0.7), or high (>0.7) likelihood of ACS. Results: Comparing fasciotomy (the diagnostic standard) and the expert panel's assessment as the diagnostic classification (test), the expert panel's determination of uncertain or high likelihood of ACS (threshold >0.3) had a sensitivity of 0.90 (0.70, 0.99), specificity of 0.95 (0.90, 0.98), PPV of 0.70 (0.50, 0.86), and NPV of 0.99 (0.95, 1.00). When a threshold of >0.7 was set as a positive diagnosis, the expert panel assessment had a sensitivity of 0.67 (0.43, 0.85), specificity of 0.98 (0.95, 1.00), PPV of 0.82 (0.57, 0.96), and NPV of 0.96 (0.91, 0.98). Conclusion: In our study, the retrospective assessment of an expert panel of the likelihood of ACS has good specificity and excellent NPV for fasciotomy, but only low-to-moderate sensitivity and PPV. The discordance between the expert panel–assessed likelihood of ACS and the decision to perform fasciotomy suggests that concern regarding potential diagnostic bias in studies of ACS is warranted. Level of Evidence: Diagnostic Level I. See Instructions for Authors for a complete description of levels of evidence.